PENDAMPINGAN DIGITAL MARKETING UKM MADU CITAYEUM DESA CIBODAS KABUPATEN MAJALENGKA - Melia Wida Rahmayani; Wulan Riyadi; Nita Hernita (Universitas Majalengka, 2022)
Madu Citayeum UKM has the potential to develop its business. Therefore, there is a need for assistance to support this, especially regarding digital marketing which is currently very much needed in the business world in various fields. This Digital Marketing assistance is expected to be able to contribute in the process of maximizing sales. Given the advancement of technology today, Madu Citeyeum SMEs are required to follow technological developments, namely by following the digital market in order to increase sales. Assistance on Digital Marketing was held in 2 (two) meetings. After the mentoring, the PKM team continued to monitor the impact of the changes that had occurred in relation to Digital Marketing that had been conveyed. Every month 2 times monitoring the development of online sales by visiting the business place of UKM Madu Citayeum, Cibodas Village.